2022
DOI: 10.3390/en15197069
|View full text |Cite
|
Sign up to set email alerts
|

An Accuracy Prediction Method of the RV Reducer to Be Assembled Considering Dendritic Weighting Function

Abstract: There are many factors affecting the assembly quality of rotate vector reducer, and the assembly quality is unstable. Matching is an assembly method that can obtain high-precision products or avoid a large number of secondary rejects. Selecting suitable parts to assemble together can improve the transmission accuracy of the reducer. In the actual assembly of the reducer, the success rate of one-time selection of parts is low, and “trial and error assembly” will lead to a waste of labor, time cost, and errors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our previous studies about DD observed faster speeds of nonlinear mapping using DD [8]. Due to the white-box attribute, controllable precision, and lower time complexity, DD was comprehensively applied in the areas of energy, traffic, weather, and physical design [9][10][11][12][13][14][15]. However, there has still been a redundant calculation in DD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies about DD observed faster speeds of nonlinear mapping using DD [8]. Due to the white-box attribute, controllable precision, and lower time complexity, DD was comprehensively applied in the areas of energy, traffic, weather, and physical design [9][10][11][12][13][14][15]. However, there has still been a redundant calculation in DD.…”
Section: Discussionmentioning
confidence: 99%
“…Literature [13] An Accuracy Prediction Method of the RV Reducer to Be Assembled Considering Dendritic Weighting Function Literature [14] An Adaptive Dendrite-HDMR Metamodeling Technique for High-Dimensional Problems…”
Section: Applications Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [23] based on the design tolerance, the relationship between each error and transmission error is established, and a prediction model of transmission error is established accurately. Jin et al [24] took the key component size parameters that affect the backlash error of the reducer as input and established a dendritic neural network prediction model to predict the backlash error. Jin et al [25] established a prediction model for the manufacturing error and backlash error of key parts in the RV-40E reducer.…”
Section: Introductionmentioning
confidence: 99%